Anti-cancer Therapies Employing IL-2 Cytokine Tumor Targeting: Contribution of Innate, Adaptive and Immunosuppressive Cells in the Anti-tumor Efficacy - Mortara, Lorenzo; Balza, Enrica; Bruno, Antonino; Poggi, Alessandro; Orecchia, Paola; Carnemolla, Barbara (Frontiers in Immunology, 2018)
Antibody-cytokine fusion proteins (immunocytokine) exert a potent anti-cancer effect; indeed, they target the immunosuppressive tumor microenvironment (TME) due to a specific anti-tumor antibody linked to immune activating cytokines. Once bound to the target tumor, the interleukin-2 (IL-2) immunocytokines composed of either full antibody or single chain Fv conjugated to IL-2 can promote the in situ recruitment and activation of natural killer (NK) cells and cytotoxic CD8+ T lymphocytes (CTL). This recruitment induces a TME switch toward a classical T helper 1 (Th1) anti-tumor immune response, supported by the cross-talk between NK and dendritic cells (DC). Furthermore, some IL-2 immunocytokines have been largely shown to trigger tumor cell killing by antibody dependent cellular cytotoxicity (ADCC), through Fcγ receptors engagement. The modulation of the TME can be also achieved with immunocytokines conjugated with a mutated form of IL-2 that impairs regulatory T (Treg) cell proliferation and activity. Preclinical animal models and more recently phase I/II clinical trials have shown that IL-2 immunocytokines can avoid the severe toxicities of the systemic administration of high doses of soluble IL-2 maintaining the potent anti-tumor effect of this cytokine. Also, very promising results have been reported using IL-2 immunocytokines delivered in combination with other immunocytokines, chemo-, radio-, anti-angiogenic therapies, and blockade of immune checkpoints. Here, we summarize and discuss the most relevant reported studies with a focus on: (a) the effects of IL-2 immunocytokines on innate and adaptive anti-tumor immune cell responses as well as immunosuppressive Treg cells and (b) the approaches to circumvent IL-2-mediated severe toxic side effects.